How the Strength of Monsoon Winds Shape Forest Dynamics - Chen-Chia Ku; Kuo-Jung Chao; Guo-Zhang M. Song; Huan-Yu Lin; Su-Wei Fan; Wei-Chun Chao (Diversity, 2022)
Monitoring long-term forest dynamics can improve our understanding of how tree species change under varying environmental conditions over time. The Nanjenshan Nature Reserve, located in the southernmost part of Taiwan, is covered by natural tropical forest and affected by the northeast monsoon wind in the winter. To explore how monsoon wind shapes the structure of vegetation, we used the long-term data of the Lanjenchi plot (high wind exposure forest) and Nanjenshan plot I (low wind exposure forest) located in the Nanjenshan Nature Reserve. In these two plots, all free-standing trees with diameter at breast height (DBH) ≥ 1 cm were identified, measured, and mapped five times in thirty years (1989–2019). Temporal changes of tree abundance, dominance, recruitment, and mortality were calculated for all species. We recorded 9694 ± 3924 individual ha−1 belonging to 126 species in the high wind exposure forest and 4019 ± 1791 individual ha−1 belonging to 105 species in the low wind exposure forest in the latest census (census 5). From 1989 to 2019, stem density in the high wind exposure forests decreased (from 12,179 ± 6689 to 9694 ± 3924 individual ha−1), while stem density in the low wind exposure forests increased (from 3253 ± 1208 to 4019 ± 1791 individual ha−1). The stem density of the rare species, which survived only in the high wind exposure forest, decreased over time. However, the basal areas of these two forests barely changed during the study periods. Due to environmental conditions, the two forests have developed different forest structures in spaces and time. Species stem density in the high wind exposure forest and diversity could continually decrease and affect the maintenance of species diversity in the monsoon wind-shaped forest.